Surface Environment of Phobos and Phobos Simulant UTPS - Miyamoto, Hideaki; Niihara, Takafumi; Wada, Koji; Ogawa, Kazunori; Senshu, Hiroki; Michel, Patrick; Kikuchi, Hiroshi; Hemmi, Ryodo; Nakamura, Tomoki; Nakamura, Akiko M.; Hirata, Naoyuki; Sasaki, Sho; et al. (Earth, Planets and Space, 2021)
The Martian Moons eXploration (MMX) mission will study the Martian moons Phobos and Deimos, Mars, and their environments. The mission scenario includes both landing on the surface of Phobos to collect samples and deploying a small rover for in situ observations. Engineering safeties and scientific planning for these operations require appropriate evaluations of the surface environment of Phobos. Thus, the mission team organized the Landing Operation Working Team (LOWT) and Surface Science and Geology Sub-Science Team (SSG-SST), whose view of the Phobos environment is summarized in this paper. While orbital and large-scale characteristics of Phobos are relatively well known, characteristics of the surface regolith, including the particle size-distributions, the packing density, and the mechanical properties, are difficult to constrain. Therefore, we developed several types of simulated soil materials (simulant), such as UTPS-TB (University of Tokyo Phobos Simulant, Tagish Lake based), UTPS-IB (Impact-hypothesis based), and UTPS-S (Simpler version) for engineering and scientific evaluation experiments.